Future perspectives of flexible ureteroscopy - Secker, Armin Josef; Rassweiler, Jens; Neisius, Andreas (Current opinion in urology, 2019)
Purpose of review: In the recent past, there were numerous and promising technological developments in the field of endourology leading to tremendous changes in the management of urolithiasis. This review will try to weave ancient stone therapy with the very modern advent of flexible ureteroscopy and recent developments in robotic systems. - Recent findings: In the broad field of flexible ureteroscopy for stone surgery, new disposable scopes have been developed and established. The use of robotic instruments is also a new and interesting concept. Additionally, clinical research on the understanding of laser features leads to a specific and appropriate use of lasers for lithotripsy, both holmium, and nowadays also interestingly thulium. - Summary: Disposable, digital flexible ureteroscopes for the treatment of both ureteric and kidney stones are taking an essential role in the medical field. Until recently, the clinically relevant laser systems for stone surgery during ureteroscopy are mainly based on Holmium laser YAG (Ho:YAG) devices, but a new thulium variant with promising features is giving interesting results. Additional research in laser features will guide to a better, more effective and safer treatment algorithm. Robotic technologies are promising but their definitive role still needs to be determined.